Impact of the Covid-19 Pandemic on Anxiety Levels in Dental Clinic A.W. Sjahranie General Hospital Samarinda - Cristiani Nadya Pramasari; Nydia Hanan; Portuna Putra Kambaya; Ruslim, Andre Kusuma (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2021)
Background: The Covid-19 is a viral infection caused by the novel coronavirus and interpersonal transmission occurs mainly via respiratory droplets and contact transmission. In some countries, the recommendations of the dental associations are to interrupt elective dental treatments, so only emergency or urgent cases are allowed. However, many patients are not aware of whether or not to attend their appointments at the dental clinic. Most of the patients are anxious but some patients feel calm to seek dental treatment. Purpose: This research is to find out the impact of the Covid-19 pandemic on anxiety levels and patient’s visit in Dental and Oral Clinic, A.W. Sjahranie General Hospital Samarinda. Materials and Method: This research was designed by the descriptive observational approach using a cross-sectional research design. The samples were new patients of child and adult who visited Dental and Oral Clinic, A.W. Sjahranie General Hospital Samarinda. The research was conducted through questionnaires to measure anxiety levels about Covid-19 pandemic conditions and the average anxiety level of patients associated with